2015
DOI: 10.7589/2014-09-230
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Reptiles Admitted to the Australian Wildlife Health Centre, Healesville Sanctuary, Australia, 2000–13

Abstract: Medical records of 931 reptiles admitted to the Australian Wildlife Health Centre, Healesville Sanctuary, Healesville, Victoria, Australia, from 2000 to 2013 were reviewed to determine the causes of morbidity and mortality. Thirty-nine species were presented; the most common were the common long-neck turtle (Chelodina longicollis; n = 311, 33.4%), the eastern bluetongue lizard (Tiliqua scincoides; n = 224, 4.1%), the blotched bluetongue lizard (Tiliqua nigrolutea; n = 136, 14.6%), and the lowland copperhead (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 10 publications
8
27
2
Order By: Relevance
“…Dog attacks were another CFA resulting in significant mortality, with reptiles highly represented in this category. This is in agreement with another Australian study that showed around 49.2-52.4% of admissions of bluetongue lizards, which are common in backyards, were admitted following dog attacks, and 70% of all dog attack admissions did not recover [8]. A study in Tennessee however, reported far fewer admissions (only 6.1%) of reptiles due to dog attacks, where "human-induced trauma" was listed as the most common CFA for reptiles [24].…”
Section: Human Activities Are Contributing To the Decline Of Australisupporting
confidence: 89%
See 1 more Smart Citation
“…Dog attacks were another CFA resulting in significant mortality, with reptiles highly represented in this category. This is in agreement with another Australian study that showed around 49.2-52.4% of admissions of bluetongue lizards, which are common in backyards, were admitted following dog attacks, and 70% of all dog attack admissions did not recover [8]. A study in Tennessee however, reported far fewer admissions (only 6.1%) of reptiles due to dog attacks, where "human-induced trauma" was listed as the most common CFA for reptiles [24].…”
Section: Human Activities Are Contributing To the Decline Of Australisupporting
confidence: 89%
“…There is substantive evidence to suggest that anthropogenic factors are having devastating consequences on native fauna, both in Australia [1][2][3][4][5][6][7][8][9] and internationally [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In part, the mission of these organizations is to treat injured and orphaned animals so that they might be returned with full function to the wild where they may continue to contribute to the population. Cat interaction is consistently a leading cause of patient admissions in the wildlife rehabilitation community (WILD‐ONe database, Wildlife Center of Virginia, Waynesboro, VA); however, incidence reporting in the peer‐reviewed literature is usually limited to specific time periods, number of individuals admitted (i.e., patients), and outcome or disposition (e.g., released, died, euthanized, permanent placement; Jessup , Schenk and Souza , Scheelings ). Although it is not appropriate to use these incident data to assess trends at the population level, they provide valuable insight into the species and life stages most affected, temporal and geospatial trends associated with free‐roaming cat interactions, and mortality associated with injuries.…”
Section: Summary Of Study Categories and Research Hypotheses Regardinmentioning
confidence: 99%
“…Conception and implementation of effective conservation management strategies should be guided by a thorough understanding of the underlying causes of wildlife population decline [18, 19, 4648]. Evaluation of longitudinal data from wildlife rehabilitation centres (WRC), including causes of admission and resultant outcomes, can be used to conduct general wildlife monitoring and investigate threats to local species [68, 13, 18, 19, 23, 24, 26, 47, 49–53], and may provide information about ecosystem health and stability [53, 54], quantify and delineate natural and anthropogenic elements that present potential hazards to wildlife survival.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using WRC admissions data has generally concentrated on either a single species or narrow taxonomic clusters [68, 15, 17, 20, 23, 50, 55, 56], with understandable foci on threatened taxa. Others have focused on particular threats, such as cat attacks, land clearing and emerging diseases [16, 21, 22, 25, 57], which have increased as human activities have encroached on wildlife habitat [26, 58].…”
Section: Introductionmentioning
confidence: 99%